Fever of unknown origin, blood and cerebrospinal fluid involvement: a leprosy case report - Chen, Huan; Jiang, Yumeng; Shi, Ying; Zhang, Wenyue; Jiang, Haiqin; Wang, Zhenzhen; Zeng, Rui; Wang, Hongsheng (Frontiers in Immunology, 2024)
Leprosy is a chronic infectious disease that mainly affects the skin and peripheral nerves, it can also invade deeper tissues and organs, including mucous membranes, lymph nodes, testes, eyes, and internal organs.Severe cases can result in deformities and disabilities. We encountered the case of a 39-year-old male with unexplained fever, headache and rash. The patient's lesions were taken for histopathological examination and slit skin smear analysis. Further, the patient was detected of Mycobacterium leprae ( M.leprae)leprosy nucleic acid sequences in the cerebrospinal fluid (CSF) and plasma, and M.lepraeleprosy gene targets in the skin lesion tissue and blood. The patient was eventually diagnosed with multibacillary leprosy and type II leprosy reaction. These results suggest the possibility of bacteremia in patients with leprosy to some extent, and observation implies the potential invasion of CSF by M.leprae or its genetic material.